Tinjauan Yuridis Penyidikan Tindak Pidana Asusila Terhadap Anak dalam Perspektif Restorative justice - Nanindya Nataningrum (Asas Wa Tandhim: Jurnal Hukum, Pendidikan Dan Sosial Keagamaan, 2026)
Sexual offenses against children have encouraged the emergence of the idea of ​​implementing restorative justice as an alternative in resolving cases which emphasizes justice and victim recovery. This study aims to analyze the legal basis for the application of Restorative justice in cases of sexual offenses against children during the investigation process, examine the implementation of its principles, and identify the resulting legal consequences. The study uses a normative juridical approach conducted through library research and supported by qualitative analysis. The application of Restorative justice is legally grounded in the Circular Letter of the Chief of the Indonesian National Police No. SE/2/II/2021. In cases of sexual crimes against children, the protection of children’s rights is prioritized as regulated in the Child Protection Law. Sexual offenses against children are categorized as serious crimes under Law No. 17 of 2016 and such cases are excluded from Restorative justice mechanisms, while perpetrators remain liable to criminal sanctions in accordance with laws.